Social Policy and Human Development: A Never-Ending Issue - Mashudi; Malta; Irena Novarlia; Ardhana Januar Mahardhani; Dedi Muliadi (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2023)
Community welfare is one of the objectives that the state must meet. Through social policy, then human development can be carried out. This human development in the future will improve the quality of people’s lives. This research will be carried out to look at how social welfare is increased through social policies to develop humans. This research will use a qualitative approach. The research data comes from the results of previous research and studies which still have relevance to the contents of this study. The results of this study found that in order to develop humans, policies and planning are unavoidable. Human development to create social welfare can be carried out with social policies supported by appropriate budgets. Acceleration of human development itself can be carried out by implementing social empowerment and community-based social rehabilitation for problem groups.